Multicriteria selection of project managers by applying grey criteria - Zavadskas, Edmundas Kazimieras; Turskis, Zenonas; Tamošaitienė, Jolanta; Marina, Valerija (Technological and Economic Development of Economy, 2008)
There is a number of criteria and associated sub‐criteria influencing the match of managers to construction projects. Criteria and sub‐criteria were identified based on a thorough review of the related literature and interviews of management personnel involved in the project managers selection. Project managers characteristics are considered to be less important for an effective project management. The model is based on multicriteria evaluation of project managers. The evaluation embraces the identified criteria influencing the process of construction project manager selection. This paper considers the application of grey relations methodology to defining the utility of alternatives, and offers a multiple criteria method of Complex Proportional Assessment of alternatives with grey relations (COPRAS‐G) for analysis. In this model, the parameters of the alternatives are determined by the grey relational grade and expressed in terms of intervals. A case study presents the selection of construction project manager. The results obtained show that this method may be used as an effective decision aid in multicriteria selection.Projektų valdytojo parinkimo daugiatikslio vertinimo modelisSantrauka. Rodiklių ir susietų subrodiklių skaičius daro poveikį statybos projektų vadovo parinkimui. Išnagrinėjus literatūrą buvo atrinkti pagrindiniai rodikliai, turintys įtaką projektų valdytojo atrankai. Išskirtos svarbiausios projektų valdytojo charakteristikos, gerinančios efektyvų statybos projektų valdymą. Projektų valdytojo modelis pagrįstas daugiatikslio vertinimo metodais. Straipsnyje apžvelgtas intervalais išreikštų sprendinių metodologijos pritaikymas, apibrėžtas alternatyvų naudingumas. Pateiktas daugiatikslio vertinimo kompleksinio proporcingumo įvertinimo metodas naudojant intervalais išreikštus rodiklius intervalais (COPRAS-G). Pateikiamame modelyje alternatyvų parametrai išreikšti intervalais, alternatyvos ranguojamos, nustatomas jų prioritetas. Sprendžiamas uždavinio pavyzdys rodo efektyvų statybos projektų valdytojo parinkimą. Tai iliustruoja gauti rezultatai.Reikšminiai žodžiai: COPRAS, sprendiniai, išreikšti intervalais, valdytojas, parinkimas.First published online: 21 Oct 2010